Attachment of a migrated MitraClip to the left ventricular apex: A novel case report. Issue 1 (31st December 2019) - Nagai, Mirei; Kurokawa, Satoshi; Ozaki, Makoto; Nomura, Minoru
Abstract: Herein, we report a novel case of emergency surgical mitral valve replacement for severe mitral valve regurgitation (MR) following MitraClip implantation (Abbott Laboratories, Chicago, IL, USA). Recurrent MR was caused because of the migration of the clip due to the destruction of the mitral valve leaflets with Staphylococcus aureus infective endocarditis. Intra‐operative transesophageal echocardiography revealed that the clip was stuck to the left ventricular apex. Although the device could not be removed surgically, surgical repair of the valve enabled the patient to recover without any further complications.